Television and eating: repetition enhances food intake - Mathur, Utsa; Stevenson, Richard J. (Frontiers in Psychology, 2015)
Some studies find that eating with TV increases food intake while others do not. Some of this variability may reflect the engagingness of what is being watched (i.e., content). To test this we varied engagingness by manipulating content familiarity. Female participants undertook two sessions. In the ‘Different’ session they watched two different episodes of the comedy Friends, with snack food presented during the second episode. In the ‘Same’ session they viewed another episode of Friends twice in succession, with snack food presented during the second repeat showing. The three episodes of Friends used here were fully counterbalanced, so overall the only difference between the ‘Same’ and ‘Different’ sessions was whether the content of the second show was familiar or novel. As expected, 14% less was eaten in the ‘Different’ session, suggesting that novel and presumably more engaging content can reduce intake relative to watching familiar and presumably less engaging content. These findings are consistent with the idea that the engagingness of TV can differentially affect food intake, although boredom or irritability resulting from repeat viewing might also explain this effect.